Home is the lootn ; Circus tricks ; Introducing Salakay [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1995)
The Marcos family robbed the country of billions of dollars making the Philippines as the sick man of Asia. Tackles the Russian circus conflict. Salakay in a school in UP Diliman with no grades, classrooms, quizzes and with one teacher emphasizing one lesson - to learn through your own hands.
Home is the loot (18 min.) -- Circus tricks (15 min.) -- Introducing Salakay (15 min.)
VHS.
Keywords: Araos, Jerry; Marcos, Ferdinand E. -- 1917-1989.; Salakay; Circus